The outcome of community-acquired pneumonia in patients with chronic lung disease (Swiss Medical Weekly, 2014)
BACKGROUND: The impact of chronic lung diseases on outcome in community-acquired pneumonia (CAP) is not well established. We aimed to investigate the outcome of adult CAP-patients with underlying chronic obstructive pulmonary disease (COPD), asthma or interstitial lung disease (ILD) in a case-control study. METHODS: We used a nationwide database including all hospitalisations in Switzerland from 2002 to 2010. Endpoints were the incidence of lung abscess, parapneumonic pleural effusion, empyema, acute respiratory distress syndrome, in-hospital mortality and length of stay. RESULTS: We found less disease-related complications of CAP in COPD (n = 17,075) and asthma (n = 2700) patients compared with their controls. This difference was mainly related to a lower incidence of pleural effusion (COPD: 4.3% vs 4.9%, p = 0.011; asthma: 3.4% vs 5.2%, p